Risk factors for coronary heart disease and family medicine – what can be done? - Mihajlović, Dalibor; Mihajlović, Biljana; Todorović, Nevena; Maksimović, Žana M (Scripta Medica, 2021)
Background / Aim: More people die each year due to cardiovascular diseases (CVDs) than from any other cause. The most common cause of ischaemic heart diseases (IHD) is atherosclerosis of the coronary arteries. Risk factors for the development of coronary heart disease (CHD) can be preventable and non-preventable. The aim of the study was to determine the frequency of individual risk factors in patients with CHD. Methods: Retrospective analysis included patients with diagnoses of stable angina pectoris (AP), unstable angina pectoris and myocardial infarction - acute coronary syndrome (ACS) and ischaemic cardiomyopathy (iCMP). The prevalence of the following risk factors for IHD was analysed: hypertension, diabetes, obesity, cholesterol, smoking, family history, age and sex. Data were taken from the Register of Patients with Chronic Diseases and Risk Factors and electronic patient records. Results: Of the total number of respondents older than 18, 4.95 % had CHD. Of the 178 patients with IHD, 70 (39.3 %) patients had AP, 60 (33.7 %) patients had ACS and 48 (27.0 %) patients had iCMP. Positive family history had 63.5 % of patients, 72 % were older than 66, 24.1 % were smokers and 74.2 % of patients had elevated blood cholesterol levels. Diabetes mellitus affected 29.2 % of patients, hypertension 88.8 %, and BMI ≥ 25 kg/m2 had 70.8 % of patients. Of the total number of patients with ACS, 68.3 % were men, while higher percentage of women suffered from AP (62.9 %) (p = 0.002). In the age below 65, CHD was more common in men (p = 0.007). Cholesterol was elevated more often in patients with AP than iCMP (p = 0.001). Patients with ACS were more likely to have diabetes mellitus compared to patients with AP and iCMP (p = 0.010). Conclusion: The prevalence of preventable risk factors is alarmingly high. Of particular importance is the timely detection and treatment of risk factors by family physicians and strengthening the personal responsibility of each individual in choosing their lifestyle and active involvement in the therapeutic process.